The Role of Musyrif’s Da’wah Communication in Enhancing Students’ Worship Awareness at Pesantren Tahfidz Wahdah Islamiyah - Iskandar; Samsuddin Samsuddin; Agusman; Azizah (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This study aims to analyze the role of musyrif’s da’wah communication in enhancing students’ worship awareness at Tahfidz Wahdah Islamiyah Islamic Boarding School, Cibinong. The research focuses on how musyrif’s da’wah communication fosters students’ religious consciousness through personal interaction, exemplary behavior, and continuous spiritual guidance. This research employed a descriptive qualitative method, using participatory observation, in-depth interviews, and documentation as data collection techniques. Data were analyzed using a thematic qualitative approach, which included data reduction, data presentation, and conclusion drawing. The findings reveal that musyrif plays a strategic role not only as a supervisor but also as a spiritual mentor, moral guide, and da’wah communicator who instills Islamic values through empathetic, dialogical, and exemplary communication. Personalized and reflective da’wah communication effectively nurtures genuine worship awareness rooted in internal spiritual motivation. The study concludes that the success of religious character development in Islamic boarding schools depends on the quality of interpersonal communication of the musyrif (dormitory educator) and a well-structured mentoring system. This research contributes to the development of an adaptive da’wah communication model in Islamic education settings.